Rekenaars in verpleegkunde: 'n Inleidende oorsig - M. Coetsee (AOSIS, 1984)
Computers will in future have a major influence on health services and their use in hospitals will increase rapidly. The value of automated systems to nursing will lie in combating rising costs, improving the quality of patient care and as a tool in nursing education and research. Nurses should however become computer literate and involve themselves in the development of the computer system at their place of employment to ensure that the specific needs of nurses are met during the planning stages. Without this computers could be cause for frustration and even bring about additional work.